2001
DOI: 10.1007/s00464-001-8148-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy performed under regional anesthesia in patients with chronic obstructive pulmonary disease

Abstract: In this series, laparoscopic cholecystectomy was feasible under epidural anesthesia and it eliminated the need for postoperative analgesia. We believe that this approach should be considered for patients who require biliary surgery but who are not good candidates for general anesthesia due to cardiorespiratory problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 14 publications
1
87
0
5
Order By: Relevance
“…Gramatica et al reported that all 29 patients of his study under thoracic epidural anaesthesia. The blood pressure and heart rate remained stable during the procedure [8]. Pursnani et al reported in his study of laparoscopic cholecystectomy performed under TEA in patients with chronic respiratory disease that all patients under thoracic epidural anaesthesia had no change in their cardio-respiratory status all over the procedure [9].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Gramatica et al reported that all 29 patients of his study under thoracic epidural anaesthesia. The blood pressure and heart rate remained stable during the procedure [8]. Pursnani et al reported in his study of laparoscopic cholecystectomy performed under TEA in patients with chronic respiratory disease that all patients under thoracic epidural anaesthesia had no change in their cardio-respiratory status all over the procedure [9].…”
Section: Resultsmentioning
confidence: 94%
“…Thoracic epidural anaesthesia (TEA) has been consistently shown to provide excellent pain relief, to facilitate early ambulation. Many used regional anaesthesia alone for laparoscopic cholecystectomy in patients with chronic obstructive airway disease [4,8,9]. It has been also used in other studies, alone for laparoscopic cholecystectomy in healthy patients [4,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystectomy with encouraging results 3 . In another series epidural anesthesia was used as sole technique for LC and the authors recommended it for patients who are not good candidates for general anesthesia due to cardio respiratory problems 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Epidural technique reduces opioid use, provides better muscular relaxation, shorter duration in recovery room, but, on the other hand, discomfort or shoulder pain caused by abdominal distention cannot be completely alleviated with epidural anesthesia and/or analgesia (23)(24)(25). Spinal anesthesia has been used only contemplated in patients where general anesthesia is contraindicated for laparoscopic cholecystectomy, however, a study in 3492 patients has found a number of advantages of spinal anesthesia, and it was concluded that spinal anesthesia should be the anesthesia of choice (26).…”
Section: Anesthetic Management Of Laparoscopic Surgerymentioning
confidence: 99%